Analyzing Menton Deviation in Posteroanterior Cephalogram in Early Detection of Temporomandibular Disorder - Trelia Boel; Ervina Sofyanti; Erliera Sufarnap (International Journal of Dentistry)
Introduction. Some clinicians believed that mandibular deviation leads to facial asymmetry and it also had a correlation with temporomandibular disorders (TMDs). Posteroanterior (PA) cephalogram was widely reported as a regular record in treating facial asymmetry and craniofacial anomalies. The objective of this study was to analyze the relationship of menton deviation in PA cephalogram with temporomandibular disorders (TMDs) symptoms. Materials and Methods. TMJ function was initially screened based on TMD-DI questionnaire. PA cephalogram of volunteer subjects with TMDs (n=37) and without TMDs (n=33) with mean age of 21.61±2.08 years was taken. The menton deviation was measured by the distance (mm) from menton point to midsagittal reference (MSR) horizontally, using software digitized measurement, and categorized as asymmetric if the value is greater than 3 mm. The prevalence and difference of menton deviation in both groups were evaluated by unpaired t-test. Result. The prevalence of symmetry group showed that 65.9% had no TMDs with mean of 1,815 ± 0,71 mm; in contrast, the prevalence of asymmetry group showed that 95.5% reported TMDs with mean of 3,159 ± 1,053 mm. There was a significant difference of menton deviation to TMDs (p=0.000) in subjects with and without TMDs. Conclusion. There was a significant relationship of menton deviation in PA cephalogram with TMDs based on TMD-DI index.